Salmon Calcitonin Attenuates Some Behavioural Responses to Nicotine in Male Mice - Aranäs, Cajsa; Vestlund, Jesper; Witley, Sarah; Edvardsson, Christian E.; Kalafateli, Aimilia Lydia; Jerlhag, Elisabet (Frontiers in Pharmacology, 2021)
The behavioural responses to nicotine involve appetite-regulatory hormones; however, the effects of the anorexigenic hormone amylin on reward-related behaviours induced by nicotine remain to be established. Previous studies have shown that the amylinergic pathway regulates behavioural responses to alcohol, amphetamine and cocaine. Here, we evaluated the effects of salmon calcitonin (sCT), an amylin and calcitonin receptor (CTR) agonist, on nicotine-induced locomotor stimulation and sensitisation as well as dopamine release in the nucleus accumbens (NAc) shell. Moreover, we investigated the effects of sCT on nicotine-induced reward and reward-dependent memory retrieval in the conditioned place preference (CPP) paradigm. Finally, we performed Western Blot experiments in an attempt to identify the levels of the amylin receptor components CTRa, CTRb and RAMP1 in reward-related areas of mice responding differently to repeated injections of sCT and nicotine in the locomotor sensitisation test. We found that sCT blocked nicotine’s stimulatory and dopamine-releasing effects and prevented its ability to cause locomotor sensitisation. Contrarily, sCT did not alter nicotine-induced reward or reward-dependent memory retrieval in the CPP paradigm. Lastly, sCT-nicotine treated mice from the locomotor sensitisation experiment displayed higher total CTR(a+b) levels in the reward-processing laterodorsal tegmental area (LDTg) of the brain compared to mice treated with vehicle-nicotine. Overall, the present data reveal an association between the amylinergic pathway and certain nicotine-induced behaviours in male mice, further contributing to the role of appetite-regulatory peptides in reward.